EXPLORING THE EFL STUDENTS’ REFLECTION IN MICRO TEACHING CLASS - Fatima Mutmainna; Murni Mahmud; Kisman Salija (State University of Makassar, 2023)
This study aimed to examine the students' learning strategies of reflection based on Kolb's (1984) theory and to determine the effects of reflection on students' learning in Micro Teaching classes. The subjects of this study were English students from the State University of Makassar, the Faculty of Language and Literature, the English Education study program, and Micro Teaching Class C for the 2021/2022 academic year. This research used descriptive qualitative research. The instruments of this research are documents and interviews. The results of the study show that (1) students use four learning strategies implemented by Kolb, namely Concrete Experience, Reflective Observation, Abstract Conceptualization, and Active Experimentation, (2) Four themes were generalized in terms of how reflection affects students' learning; Increasing the depth of knowledge, identifying the areas which are missing or deficient, providing comparative references in learning and helping learners build structural connections in knowledge.Keywords: Reflection, Journal Reflection, and Micro Teaching